The genus Portelmis Sanderson, 1953 (Coleoptera: Elmidae: Elminae): first report in Brazil, description of two new Amazonian species and species key for males - Fernandes, André S.; Passos, Maria Inês S.; Hamada, Neusa (Zootaxa, 2010)
The genus Portelmis Sanderson, 1953 and the species P. gurneyi Spangler, 1980 are reported for the first time in Brazil. Portelmis kinonatilis sp. nov. and P. paulicruzi sp. nov. are described and illustrated based on adult specimens collected in two different municipalities in the state of Amazonas, Brazil. Diagnoses and illustrations of all Portelmis species, and a taxonomic key to identify males are presented.